2023
DOI: 10.1186/s12984-023-01153-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bihemispheric transcranial direct current stimulation on motor recovery in subacute stroke patients: a double-blind, randomized sham-controlled trial

Abstract: Background Bihemispheric transcranial direct current stimulation (tDCS) of the primary motor cortex (M1) can simultaneously modulate bilateral corticospinal excitability and interhemispheric interaction. However, how tDCS affects subacute stroke recovery remains unclear. We investigated the effects of bihemispheric tDCS on motor recovery in subacute stroke patients. Methods We enrolled subacute inpatients who had first-ever ischemic stroke at subco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…The included studies 18–61 involved 1555 patients (experimental group: 820, control group: 715) and were published between 2010 and 2024 in 20 countries. The top three countries based on the number of research studies were Italy ( n = 10), China ( n = 9), and the United States ( n = 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies 18–61 involved 1555 patients (experimental group: 820, control group: 715) and were published between 2010 and 2024 in 20 countries. The top three countries based on the number of research studies were Italy ( n = 10), China ( n = 9), and the United States ( n = 5).…”
Section: Resultsmentioning
confidence: 99%
“…Taud et al 53 utilized anodal and bilateral stimulation for the experimental groups, while Qu et al 46 employed 1 and 2 mA of cathodal stimulation for the experimental groups. Fifteen studies 21,22,2426,29,32,37,38,42,47,50,55,56,61 exclusively utilized anodal stimulation for the experimental group, 19 1820,23,28,31,3436,39,41,43,45,51,52,54,57,58,62 exclusively utilized bilateral stimulation for the experimental group, and four 27,40,48,59 exclusively utilized cathodal stimulation for the experimental group (Table 1). Additionally, 39 studies 1823,2628,3040,42…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…presented that dual‐tDCS combined with constraint‐induced movement therapy can significantly improve FMA–UE scores in patients with chronic stroke. Hsu et al 26 . indicated that bihemispheric tDCS during task‐oriented training may facilitate motor recovery in subacute stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…24 Studies have shown that bilateral dual-tDCS can more effectively regulate cortical excitability and improve upper limb function than unilateral tDCS. [25][26][27] Furthermore, a recent systematic review and meta-analysis indicated that stimulation of the primary somatosensory cortex (PSC) showed significant therapeutic potential to improve sensorimotor function in patients with stroke. 28 Accordingly, dual-tDCS over PSC has the potential to amend inter-hemispheric imbalance in subacute stroke.…”
Section: Introductionmentioning
confidence: 99%